(untitled) (Medical Forum Monthly, 2024)
Objective: This review critically compares existing and emerging methods used to assess childhood vaccination coverage in developing countries to determine their strengths, weaknesses, accuracy, efficiency, inherent biases, and suitability based on their unique challenges. Results: The methodologies reviewed included administrative data, household surveys (Demographic Health Surveys (DHS), Multiple Indicator Cluster Surveys (MICS) and Lot Quality Assurance Sampling (LQAS), school-based assessments, and serosurveys. Administrative data often suffers from inaccuracies and data manipulation tendencies. Household surveys, especially DHS and MICS, offer detailed insights but are resource-intensive and require specialized expertise. School-based assessments, while easy to implement, face generalizability constraints. Serosurveys are resource-intensive but uniquely gauge effective vaccination coverage through immunity profiling. A novel approach such as LQAS emerges as a rapid and suitable method for resource-limited settings. MICS Plus is also a recent innovative extension that effectively assesses seasonality effects. Conclusion: This review serves as an updated guide with novel developments for policymakers, health professionals, and program implementers to make informed decisions on vaccination coverage assessment. Combining methods like LQAS with household surveys and following them with the MICS Plus model can yield optimal results for developing countries.